Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jmri.26574
|View full text |Cite
|
Sign up to set email alerts
|

Rapid single‐breath hyperpolarized noble gas MRI‐based biomarkers of airspace enlargement

Abstract: Background Multi‐b diffusion‐weighted hyperpolarized‐gas MRI measures pulmonary airspace‐enlargement using apparent diffusion coefficients (ADCs) and mean‐linear‐intercepts (Lm). Purpose To develop single‐breath 3D multi‐b diffusion‐weighted 3He and 129Xe MRI using k‐space undersampling. Rapid, cost‐efficient, single‐breath acquisitions may facilitate clinical translation. Study Type Prospective. Subjects We evaluated 12 participants, including nine subjects (mean age = 69 ± 9) who were included in the retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…25 Meanwhile, in our study, the means of SNR of images with maximum b-value of 30 s/cm 2 were 16, 23, and 21 for FS, rVCS, and rCS measurements, respectively. The lowest SNR was 13, which met the Rose criteria of SNR = 5 for the lung morphometric estimates, 39,40 and the measured SNRs for each subject are summarized in Table S4. In addition, our retrospective results suggested that the proposed method can achieve comparable image quality (MAE < 0.03) 25 and reliable lung morphological parameters (the differences were less than 3%) with the FS acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…25 Meanwhile, in our study, the means of SNR of images with maximum b-value of 30 s/cm 2 were 16, 23, and 21 for FS, rVCS, and rCS measurements, respectively. The lowest SNR was 13, which met the Rose criteria of SNR = 5 for the lung morphometric estimates, 39,40 and the measured SNRs for each subject are summarized in Table S4. In addition, our retrospective results suggested that the proposed method can achieve comparable image quality (MAE < 0.03) 25 and reliable lung morphological parameters (the differences were less than 3%) with the FS acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Nevertheless, the reconstruction of SIDER needs pre-estimated model parameters provided by the TV reconstructed results, resulting in long reconstruction time [ 12 ]. Although TV and SIDER can remove aliasing artifacts to some extent, they lead to over-smooth appearances in lung regions owing to the high acceleration factor.…”
Section: Discussionmentioning
confidence: 99%
“…Successful application of deep learning relies on large and high-quality training data, which may not be feasible for some medical imaging problems [ 40 ]. This is especially true for multiple b -value gas DW-MRI due to the limitations of non-renewable gas hyperpolarization and breath-holding duration [ 12 ]. Training on simulated data is one of the strategies to eliminate this issue and permit generating large amounts of training data with diverse experimental conditions [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, most hyperpolarized gas MRI methods require completion within a single closed breath, which can impose a considerable burden on patients due to the extended holding time. Third, the achievement of targeted modification and visualization of various molecular targets of lung cancer using hyperpolarized 129 Xe gas poses significant challenges (Abascal et al, 2018; Duan et al, 2019; Ireland et al, 2010; Westcott et al, 2018; Xiao et al, 2019). In comparison to hyperpolarized gas imaging, the utilization of nano‐particles as an intelligent and multifunctional platform for biomedical applications presents significant advantages, demonstrated by their targeted delivery of antitumor drugs, efficient capacity for drug‐loading, controllable release, and among other notable characteristics.…”
Section: Comparison With Other Existing Techniquesmentioning
confidence: 99%